Effects of Antipsychotic Medications and Illness Duration on Brain Features That Distinguish Schizophrenia Patients. (4th August 2022) - Zeng, Jiaxin; Zhang, Wenjing; Wu, Guorong; Wang, Xiaowan; Shah, Chandan; Li, Siyi; Xiao, Yuan; Yao, Li; Cao, Hengyi; Li, Zhenlin; Sweeney, John A; Lui, Su; et al.
Abstract: Background and Hypothesis: Previous studies have reported effects of antipsychotic treatment and illness duration on brain features. This study used a machine learning approach to examine whether these factors in aggregate impacted the utility of MRI features for differentiating individual schizophrenia patients from healthy controls. Study Design: This case-control study used patients with never-treated first-episode schizophrenia (FES, n = 179) and long-term ill schizophrenia (LTSZ, n = 30), with follow-up of the FES group after treatment ( n = 71), a group of patients who had received long-term antipsychotic treatment ( n = 93) and age and sex-matched healthy controls ( n = 373) for each patient group. A multiple kernel learning classifier combining both structural and functional brain features was used to discriminate individual patients from controls. Study Results: MRI features differentiated untreated FES (0.73) and LTSZ (0.83) patients from healthy controls with moderate accuracy, but accuracy was significantly higher in antipsychotic-treated FES (0.94) and LTSZ (0.98) patients. Treatment was associated with significantly increased accuracy of case identification in both early course and long-term ill patients (both p < .001). Effects of illness duration, examined separately in treated and untreated patients, were less robust. Conclusions: Our results demonstrate that initiation of antipsychotic treatment alters brain features in ways that further distinguish individual schizophrenia patients from healthy individuals, and have a modest effect of illness duration. Intrinsic illness-related brain alterations in untreated patients, regardless of illness duration, are not sufficiently robust for accurate identification of schizophrenia patients.